2019
DOI: 10.1002/jbm.a.36766
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive glasses and glass‐ceramics versus hydroxyapatite: Comparison of angiogenic potential and biological responsiveness

Abstract: Different bioactive glasses (BGs), bioceramics, and their composites were extensively analyzed in terms of biological responsiveness and angiogenic potential. In particular several inorganic materials were considered, namely the widely used 45S5 BG, an experimental BG with low tendency to crystallize, other three experimental BGs doped with strontium and/or magnesium, a commercial hydroxyapatite (HA), and two BG–HA composites (with varying percentages of BG and HA). All these materials were ad hoc prepared and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 37 publications
1
11
0
Order By: Relevance
“…In the present study, the incorporation of BG-Mg powder into the PCL matrix did not cause negative effects on cytotoxicity or inhibition of cell growth until day 21 ( Figure 7 and Figure 8 ), considering both the investigated formulations. These results agreed with the cellular viability assays of the basic materials, i.e., PCL pellets (MW = 80,000, Aldrich Chemistry) and bioactive glass powder BG-Mg with the composition (in mol%): 47.2% SiO 2 , 2.6% P 2 O 5 , 2.3% Na 2 O, 2.3% K 2 O, 35.6% CaO, and 10% MgO [ 15 , 48 ]. Referring to the bioactive glass, it exerted a strong stimuli effect on cell growth and metabolism; in particular, magnesium ion (Mg 2+ ) favours different biological processes including the regulation of active calcium transport [ 17 ].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…In the present study, the incorporation of BG-Mg powder into the PCL matrix did not cause negative effects on cytotoxicity or inhibition of cell growth until day 21 ( Figure 7 and Figure 8 ), considering both the investigated formulations. These results agreed with the cellular viability assays of the basic materials, i.e., PCL pellets (MW = 80,000, Aldrich Chemistry) and bioactive glass powder BG-Mg with the composition (in mol%): 47.2% SiO 2 , 2.6% P 2 O 5 , 2.3% Na 2 O, 2.3% K 2 O, 35.6% CaO, and 10% MgO [ 15 , 48 ]. Referring to the bioactive glass, it exerted a strong stimuli effect on cell growth and metabolism; in particular, magnesium ion (Mg 2+ ) favours different biological processes including the regulation of active calcium transport [ 17 ].…”
Section: Discussionsupporting
confidence: 80%
“…A more structured evaluation of cellular response on printed scaffold architectures shall be tested, with a combination of degradation, release, and mechanical fatigue assessments, which approach the physiological scenario. For instance, the release of ions, such as Ca 2+ ; PO 3 2− , Mg 2+ , and Si + , is interesting considering osteogenesis and angiogenesis, as reported in Rahaman, et al [ 51 ] and Bellucci, et al [ 48 ]. Finally, the in vivo behaviour should be evaluated in preclinical tests.…”
Section: Discussionmentioning
confidence: 99%
“…They can modulate the activity of stem/progenitor cells, thereby inducing new bone and/or blood vessel formation and enhancing osseointegration. [5,13,[23][24][25] Due to its biodegradable nature and mechanical properties comparable to the bone, Mg is an attractive metallic biomaterial for resorbable scaffolds intended for bone regeneration. [13,26] The presence of Mg may favor osseointegration through the recruitment of bone marrow stromal stem cells [13] and more recent research has indicated its angiogenic potential through the upregulated expression of angiogenic factors.…”
Section: Introductionmentioning
confidence: 99%
“…In the past decade, the development of particle drug-delivery systems has been the main focus of drug-loading research. Among these systems, bioceramic particles have attracted more and more attention due to their excellent biocompatibility [1], bioaffinity [2], biological activity [3], high stability [4], and sufficient mechanical properties [5]. Hydroxyapatite is a calcium phosphate bioceramic [6] that is widely used as a bone substitute because nanohydroxyapatite particles (n-HAPs) are one of the components of natural bone [7].…”
Section: Introductionmentioning
confidence: 99%